PEMANFAATAN MEDIA CANVA DALAM UPAYA MENINGKATKAN MINAT BELAJAR PESERTA DIDIK KELAS 8E DI SMP NEGERI 22 SURABAYA - Oxin Oktarina Widita, Putu; Rizqiyah, Rizqiyah; Mila Sukma, Ratnasari; Nanik Setyowati, RR.; Masnidar, Masnidar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine the effectiveness of using Canva media in increasing the learning interest of class 8E students at SMPN 22 Surabaya in social studies subjects. This research was conducted because: (1) students were less active in participating in learning activities (2) less enthusiastic in answering questions (3) did not pay attention to the teacher's explanation. This research was conducted at SMP Negeri 22 Surabaya in class 8E with a total of 32 respondents. This research is Classroom Action Research (PTK). The data collection techniques in this research were observation techniques and questionnaires to students regarding the Canva media which had been implemented in class during cycle 1 and cycle 2. The research results showed effective results in implementing the learning process using Canva media. Students' interest in learning increased from cycle 1 to cycle II. The results of student learning activities in cycle I reached 2.4% and increased in cycle II by 3.8%. Apart from the results of students' learning activities, there was an increase in students' interest in learning obtained from the results of questionnaire data processing. In the first cycle, the results of filling out the questionnaire were 2.9% with sufficient interest and experienced a significant increase in the second cycle, namely 3.7% in the very interested category. The use of Canva media in social studies lessons on financial institutions is very popular with class 8E students.